Protein Structure Prediction with AlphaFold2, How it Works, Limitations and Solution for Less number of Homotypic and Large number of Heterotypic Contacts - Hassan Kaleem; Muhammad Noman Khalid (Innovative Computing Review, 2022)
Knowing the protein structure helps us to investigate diseases in human beings related to abnormal or impaired folded proteins. This research provides a solution for how to identify the misbalance of homotypic and heterotypic contacts on the sequential stage. There are two methods of protein structure prediction, template based and Ab-initio models. Template based model matches the given sequence with the original sequence. Whereas, Ab-initio calculates the weight of the given sequence and identifies whether it is balanced or not. If the sequence is not in balance, it can be labeled as on the initial stage by calculating its weight. In this research, future directions to researchers are provided as how to achieve maximum accuracy in protein structure prediction.